Elisa indireto com proteinas recombinantes para diagnóstico da infecção por Brucella ovis em carneiros - Silvia de Araujo Franca (2014)
Brucella ovis is a major cause of epididymitis in sexually mature rams, resulting in subfertility, infertility, and economic losses for the sheep industry worldwide. The aim of this study was to develop an indirect ELISA (iELISA) using recombinant proteins, namely rBoP59 or rBP26, as antigens for serological diagnosis of B. ovis infection. rBoP59 and rBP26 were purified by affinity chromatography and antigenicity of these was tested by Western blot and iELISA. The tests of repeatability and reproducibility were performed with 500 ng and 1 g of BoP59r or BP26r per well, testing serum from negative and positive rams in AGID, bacteriology and PCR from urine samples, being performed 10 separate repetitions. BoP59r did not discriminate negative from positive, but BP26r was effective in distinguishing positive from negative ram serum samples. The ELISAi with BP26r using sera from rams experimentally infected with B. ovis had the highest performance with serum dilution of 1:20, with 100% sensitivity, 90.2% specificity, positive predictive value (PPV) of 93.2%, negative predictive value (NPV) of 100%, and accuracy of 1.0. For serum samples that had been positive by AGID, best results were obtained from the serum dilution at 1:40, the sensitivity was 85.7%, specificity 85.4%, PPV of 75%, VPN of 92.1% and accuracy was 0.9029. And the results indicate that BP26r is a good serological marker for B. ovis infection in sheep.